Early origins of divergent patterns of morphological evolution on the mammal and reptile stem-lineages - Brocklehurst, N; Ford, D; Benson, RBJ (Oxford University Press, 2022)
The origin of amniotes 320 million years ago signalled independence from water in vertebrates and was closely followed by divergences within the mammal and reptile stem lineages (Synapsida and Reptilia). Early members of both groups had highly similar morphologies, being superficially ‘lizard-like’ forms with many plesiomorphies. However, the extent to which they might have exhibited divergent patterns of evolutionary change, with potential to explain the large biological differences between their living members, is unresolved. We use a new, comprehensive phylogenetic dataset to quantify variation in rates and constraints of morphological evolution among Carboniferous–early Permian amniotes. We find evidence for an early burst of evolutionary rates, resulting in the early origins of morphologically distinctive subgroups that mostly persisted through the Cisuralian. Rates declined substantially through time, especially in reptiles. Early reptile evolution was also more constrained compared to early synapsids, exploring a more limited character state space. Postcranial innovation in particular was important in early synapsids, potentially related to their early origins of large body size. In contrast, early reptiles predominantly varied the temporal region, suggesting disparity in skull and jaw kinematics, and foreshadowing the variability of cranial biomechanics seen in reptiles today. Our results demonstrate that synapsids and reptiles underwent an early divergence of macroevolutionary patterns. This laid the foundation for subsequent evolutionary events and may be critical in understanding the substantial differences between mammals and reptiles today. Potential explanations include an early divergence of developmental processes or of ecological factors, warranting cross-disciplinary investigation.